2011
DOI: 10.4236/oji.2011.12004
|View full text |Cite
|
Sign up to set email alerts
|

Functions of hereditary immunity and xenogamy in cancer origin and pandemic spread

Abstract: The efficacy of means exploited currently for cancer prevention and treatment appeared to be very low. New insights into the origin of the disease are sorely needed. The present article synthesizes the results from integrative reconsideration of actual data on cancer from the viewpoint of recent developments in pathology, epidemiology, immunology, genetics, and evolution. In contrast to the 80 years old hypothesis of somatic mutative origin of carcinogenesis, the revealed set of evidence showed the origin of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Such deviant cell lineages appear in the human body as a result of genome transformation performed over the heterozygous crossbreeding between parental gametes with partially different (deviant) genotypes. In the xenogamous formation of a descendant's zygote, its genome becomes admixed with the deviant (carcinogenic) genes [5]. Xenogamous mating between members of genetically different species [29], subspecies, ethnoses and families was characteristic of the descent of humans and their further evolution as they wandered the world.…”
Section: Origin Of Cancerous Contagionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such deviant cell lineages appear in the human body as a result of genome transformation performed over the heterozygous crossbreeding between parental gametes with partially different (deviant) genotypes. In the xenogamous formation of a descendant's zygote, its genome becomes admixed with the deviant (carcinogenic) genes [5]. Xenogamous mating between members of genetically different species [29], subspecies, ethnoses and families was characteristic of the descent of humans and their further evolution as they wandered the world.…”
Section: Origin Of Cancerous Contagionmentioning
confidence: 99%
“…It was supposed that cancerous units in primordially different locations become clinically detectable at different times after the initiation of malignant growth; this allows for the differences in their initially smaller sizes. The differences in initial cancer cell masses and their subunits throughout the body predestine individual diversity in the course and severity of cancer when the disease begins to develop [5].…”
Section: Heterogenic Make-up Of a Ripe Cancermentioning
confidence: 99%
“…Human cancer possesses its own schedule (the program of ontogenesis) as well as the abilities of communication and physiological synchronization between its intra-host subunits. The existence of these intrinsic traits has been initially estimated [4,5,23,24] with detailed presentation and discussion of the evidence. Later, it has been experimentally shown that the spread of melanoma in the mouse model correlated with the eventual progress of the disease in human patients.…”
Section: Human Cancer Arises Via Intrusion a Victimmentioning
confidence: 99%
“…The deviant cells appear in a human body as the result of genome transformation performed over the heterozygous crossbreeding between parental gametes with partially different (divergent) genotypes [24]. This is a kind of chimerism or cellular mosaicism, the occurrence in an [25,26].…”
Section: Human Cancer Arises Via Intrusion a Victimmentioning
confidence: 99%
“…This clone is foreign (non-self) for the afflicted body with many of its traits. The deviant cells appear in a human body as the result of genome transformation performed over the heterozygous crossbreeding between parental gametes with partially different (divergent) genotypes [9]. This is a kind of chimerism or cellular mosaicism, the occurrence in an individual of two or more cell clones of different genome constitutions, derived from different parental individuals [31,32].…”
Section: Human Cancer Arises Via Intrusion a Victim Genomementioning
confidence: 99%